(untitled) - Sekhawat, Kirti

Evaluating the effect of oxygen addition on yeast physiology, population dynamics and wine chemical signature in controlled mixed starter fermentations (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.